Exploring Microbial Biosignatures in Mn-Deposits of Deep Biosphere: A Preliminary Cross-Disciplinary Approach to Investigate Geomicrobiological Interactions in a Cave in Central Italy - Vaccarelli, Ilaria; Matteucci, Federica; Pellegrini, Marika; Bellatreccia, Fabio; Del Gallo, Maddalena (Frontiers in Earth Science, 2021)
The terrestrial subsurface offers privileged sites both to search for microbial life and to observe still mostly unknown characteristic lithologies. In particular, caves represent natural laboratories to investigate unique minerogenetic processes and biotic interactions, connected to these phenomena. Manganese mineralization in cave environments provides a window to understand the complex Mn cycle and the development of microbial communities in special conditions, such as low constant temperature, absence of light and, in particular, low-energy environments. In the current study, we isolated and characterized Mn-samples taken from the cave “Grotta Grande dei Cervi”, L’Aquila, Central Italy, and we used a multidisciplinary approach to characterize them, with the purpose of understanding the biogeochemical processes in extreme environments. A chemical characterization of the samples was done by EDS; further investigations are underway with other multidisciplinary methodologies to understand whether the Mn laminae are related to biological processes. SEM investigations revealed microbial imprints, showing cell-like structures and suggesting that the cell-like shapes occur within internal laminae. A culture-independent approach was used to assess the possibility that biotic factors may be involved in the production of these mineralizations and to investigate the nature of the microbial community in these materials. A molecular approach was the first step to investigate the role of microorganisms in forming manganese oxides associated with water bearing rocks. DNA from the black deposits was extracted and sequence analyses of specimens were performed. Our data support the hypothesis that microorganisms may contribute to the mineralizations of manganese in this environment, providing new encouraging insight into the role of microorganisms in the Mn cycle and the processes of energy acquisition in unfavorable conditions, with relevant implications for astrobiology.